Customer Perception towards Green Products in Pokhara Valley - Lamichhane, Baburam (Janapriya Journal of Interdisciplinary Studies, 2022)
This study aims to explore customer awareness and perception towards green products in Pokhara valley. It focuses on customer perception on price, quality, availability, and promotional strategy of green products. For this purpose, the sample size was taken from the entire population of Green Product users in Pokhara Valley. Among them, 110 respondents have been selected on non-probability purposive sampling technique for determining sample size. Primary data was collected by using of structural questionnaire from the targeted respondents. Data analysis was done using the SPSS tool. Descriptive analysis was used for analyzing data. The majority of respondents feel green products as environmentally friendly and healthy and safe products. They declared that they mostly purchase organic food. An advertisement was an important source for providing information about green products to the customers. The majority of customers were not having a precise opinion about the excessive prices of green products but a larger portion were agreed to pay more for green products and to purchase green products in case of the same price as non-green products. Customers were satisfied with the quality of green products. They were aware of their harmless nature of them. They were dissatisfied with the availability of green products. Most of the respondents possessed a very pessimistic opinion towards the promotional strategies of green products. They agreed to take environmental consideration and read the product’s label while buying these products. This study contributes to analyzing the customers’ perception towards Marketers and manufacturers and mainly focuses on the improvement of the quality of green products and making it convenient to buy through increasing its availability and accessibility.